2016
DOI: 10.1002/art.39766
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Signs of Spondyloarthritis in First‐Degree Relatives of HLA–B27–Positive Ankylosing Spondylitis Patients: The Pre‐Spondyloarthritis (Pre‐SpA) Cohort Study

Abstract: A substantial proportion of seemingly healthy first-degree relatives of HLA-B27-positive AS patients have clinical and/or imaging abnormalities suggestive of SpA. Thirty-three percent could be classified as having SpA. Further follow-up will show which first-degree relatives will develop clinically manifest SpA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…For this study, all participants from the pre-spondyloarthritis (Pre-SpA) cohort, known to have an increased risk to develop SpA, were approached regardless of their time of follow-up. This cohort has been described in detail previously [10]. In short, pre-SpA is an ongoing, prospective, multicenter inception cohort of healthy, first-degree relatives of HLA-B27positive axSpA patients between 18 and 40 years of age.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, all participants from the pre-spondyloarthritis (Pre-SpA) cohort, known to have an increased risk to develop SpA, were approached regardless of their time of follow-up. This cohort has been described in detail previously [10]. In short, pre-SpA is an ongoing, prospective, multicenter inception cohort of healthy, first-degree relatives of HLA-B27positive axSpA patients between 18 and 40 years of age.…”
Section: Study Populationmentioning
confidence: 99%
“…Initiatives as the pre-SpA cohort [10], a prospective cohort of healthy first degree relatives of axSpA patients, and the SPACE (SPondyloArthritis Caught Early) cohort [11] might enable in a very early phase to identify, treat and thereby possibly even prevent axSpA. Therefore, also in axSpA, preventive treatment is an imaginable scenario.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the study by Turina et al confirmed a familial risk of SpA among asymptomatic first‐degree relatives of AS patients. These investigators’ findings build on the aforementioned work, and follow‐up of these subjects in a prospective manner will provide new opportunities for understanding the incidence, characteristics, and pathogenesis of AS.…”
mentioning
confidence: 76%
“…In this issue of Arthritis & Rheumatology , Turina and colleagues report findings from a prospective follow‐up cohort (called the pre‐spondyloarthritis [Pre‐SpA] cohort) of 51 seemingly healthy first‐degree relatives (ages 18–40 years) of 36 HLA–B27–positive AS patients. They have described the baseline characteristics of this group.…”
mentioning
confidence: 99%
“…We read with interest the report by Turina et al on spondyloarthritis (SpA)-related symptoms in first-degree relatives of SpA patients (1). The authors reported that one-third of first-degree relatives were classified as having SpA according to the Assessment of SpondyloArthritis international Society (ASAS) criteria (2).…”
mentioning
confidence: 99%